1980
DOI: 10.1007/bf00504539
|View full text |Cite
|
Sign up to set email alerts
|

Hexobarbital-binding, hydroxylation and hexobarbital-dependent hydrogen peroxide production in hepatic microsomes of guinea pig, rat and rabbit

Abstract: Cytochrome P-450 dependent oxygenase (3'-hydroxy-hexobarbital) and oxidase activities (hydrogen peroxide) have been measured in hepatic microsomes from guinea pigs, rats and rabbits. A sensitive gas-chromatographic assay was developed to measure the hydroxylated product 3'-hydroxy-hexobarbital. The kinetics of its formation were determined and correlated to hexobarbital type I binding and compared with oxidase activity: in the rat, Vmax for 3'-hydroxyhexobarbital formation was 5.1 and 2.6 nmoles/mg/min, resp. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
1

Year Published

1982
1982
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 20 publications
0
14
1
Order By: Relevance
“…CYP2B isoforms in particular are involved in activation of aflatoxin B1 or cyclophosphamide to genotoxic metabolites (Chang et al, 1993). Furthermore, reactive oxygen species (ROS) are released during the catalytic reaction cycle of P-450 (Heinemeyer et al, 1980). It is assumed that activity of P-450 systems constitutes a major source of intracellular ROS in the liver (Bondy and Naderi, 1994;Puntarulo and Cederbaum, 1998), indicating that excessive P-450 activity resulting from P-450 induction may lead to cellular damage caused by generation of noxious metabolites or ROS.…”
mentioning
confidence: 99%
“…CYP2B isoforms in particular are involved in activation of aflatoxin B1 or cyclophosphamide to genotoxic metabolites (Chang et al, 1993). Furthermore, reactive oxygen species (ROS) are released during the catalytic reaction cycle of P-450 (Heinemeyer et al, 1980). It is assumed that activity of P-450 systems constitutes a major source of intracellular ROS in the liver (Bondy and Naderi, 1994;Puntarulo and Cederbaum, 1998), indicating that excessive P-450 activity resulting from P-450 induction may lead to cellular damage caused by generation of noxious metabolites or ROS.…”
mentioning
confidence: 99%
“…superoxide (Ingelman-Sundberg and Johansson, 1980;Kuthan et al, 1978), hydrogen peroxide (Heinemeyer et al, 1980;Oprian et al, 1983), and water (Gorsky et al, 1984;Morgan et al, 1982;Zhukov and Archakov, 1982), respectively. In in vitro reactions, hydrogen peroxide arises in two ways: by dismutation of the superoxide anion (Equation 1) and by dissociation of hydrogen peroxide from a two-electron-reduced cytochrome P-450.…”
mentioning
confidence: 99%
“…It was found that some substrates of the monooxygenase system stimulate Hz02 formation whereas others are either not effective or are effective only in animals pretreated with phenobarbital but not with pregnenolone-16a-carbonitrile [3,4]. A correlation of H202 formation with the spectral binding and hydroxylation of hexobarbital was observed by Heinemeyer et al [6] from which a hypothetical peroxide complex of cytochrome P450 was postulated as a common intermediate for Hz02 formation and substrate hydroxylation.If this hypothesis is correct, an increased H202 formation should be observable upon addition of pseudo-substrates [7,8] of the microsomal cytochrome P450 monooxygenase system. This was reinvestigated in the present study.As a second possible pathway of NADPH-dependent formation of H202 in liver microsomes the release of superoxide anion radicals by autoxidation of microsomal redox systems, and the subsequent disproportionation of these Saarland, Homburg-Saar, Federal Republic of Germany.…”
mentioning
confidence: 99%